Underlying Concepts in the Evaluative Rationalities of School Teachers [Concepciones Subyacentes a Las Racionalidades Evaluativas de Docentes Escolares] - Rios-Munoz, D; Herrera-Araya, D (Pontificia Universidad Catolica de Chile, 2022)
In this paper, we analyze the concepts underlying the evaluative rationalities of teachers who work in school establishments. The research is of a qualitative-interpretive nature. Fifteen teachers participated, who had varying different years of work experience and were teaching different levels and subjects of the school curriculum. To collect the information, we conducted a group interview and a focus group. The data were systematized by means of content analysis with version 12 of the software NVivo. The main results reveal the prevalence of technological evaluative rationalities and cultural practice rationalities among the participating teachers. Based on these findings, we discuss the need to reflect on the implicit components that underlie evaluative rationalities and how these should be revealed and assumed in order to address new demands of assessment practice in different school contexts. © 2022 PEL.